A Case Report of a Patient With Pulmonary Arterial Hypertension Transitioned From Inhaled Iloprost to Selexipag. (December 2021) - Verlinden, Nathan J.; Walter, Claire; Raina, Amresh; Benza, Raymond L.
Pulmonary arterial hypertension (PAH) is a progressive disease characterized by elevated pulmonary vascular resistance that can lead to right ventricular failure and death. The use of medications that affect the prostacyclin pathway is an important treatment strategy in PAH. Inhaled iloprost is a prostacyclin analogue, and selexipag is an oral, non-prostanoid, prostacyclin IP receptor agonist. Data are limited on transitioning patients from inhaled iloprost to selexipag. In this case report, we describe the successful transition of a 57-year-old female with heritable PAH from inhaled iloprost to selexipag over 8 weeks in an out-patient setting. After initiation of selexipag, the patient's inhaled iloprost dose was gradually reduced and eventually discontinued. The patient tolerated the transition well with stable symptoms, 6-minute walk distance, and pulmonary hemodynamics. Additional studies are needed to better define the comparative efficacy and safety of inhaled iloprost and selexipag.